Alteration of speed-of-sound by fixatives and tissue processing methods in scanning acoustic microscopy - Tamura, Kazuki; Ito, Kazuyo; Yoshida, Sachiko; Mamou, Jonathan; Miura, Katsutoshi; Yamamoto, Seiji (Frontiers in Physics, 2023)
The elasticity of biological tissues is one of the physical characteristics of tissues and has attracted attention as a clinical diagnostic parameter. The elasticity can be determined on the microscopic scale with speed of sound (SoS) measurements using acoustic microscopy. In SoS measurements, a thin-sliced section is attached to a glass slide in the same manner as a light microscopic specimen. There are two main methods for preparing thin sections: paraffin-embedding and frozen-section. The frozen-section method requires fewer processing steps from sectioning to measurement and is considered to reduce artifacts in the sample compared with the paraffin-embedding method. Both methods need fixatives to keep tissue structures. Many reports of measurements using frozen sections are focused on soft tissues with relatively high protein contents. In this study, we determined the SoS in thin sections of four types of organs (brain, heart, liver, and kidney) prepared using two different methods (paraffin-embedding and frozen-section) and four different chemical fixatives (formalin, Karnovsky fixative (KF) 0.5% and 2.0% glutaraldehyde, and ethanol). The SoS in heart and liver samples prepared using KF showed good agreement with reported values for raw samples. For samples fixed with KF, the SoS increased as the glutaraldehyde concentration increased from 0.5% to 2.0%. A brain tumor sample was processed with KF 0.5%, and the SoS in the tumor was significantly higher than that in the non-tumor area. The results confirmed that it is possible to measure the SoS in brain samples with low protein contents using appropriate fixatives.